Justified's visual rhetoric: television's subtle unmasking of the myth of the south. Issue 4 (2nd October 2019) - Sciullo, Nick J.
Abstract: In this article, I argue that the television show Justified represents a critique of the Myth of the South. I argue that Justified critiques the representation of the U.S. South and it does so by invoking the Myth of the West, which affords viewers the opportunity to identify with something they know and in so doing makes the critique of the Myth of the South more palatable. I further argue that critiquing regional identities is necessary because these identities continue to structure much of the way we think about people and places in the United States. Through a rhetorical investigation of the Myth of the South and a critical reading of Justified, I demonstrate the ways in which the Myth of the West can help do important work to critique another popular cultural myth and that Justified is an important text to investigate because of its viewership (vis-à-vis identification and escapism), relationship to popular genres, and use of one myth to critique another.